PRODUKTIVITAS LAHAN DAN DISTRIBUSI PENDAPATAN BERDASARKAN STATUS PENGUASAAN LAHAN PADA USAHATANI PADI (KASUS DI KABUPATEN KENDAL PROPINSI JAWA TENGAH) - Mudakir, Bagio (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2011)
Ownership of farm land usually consistent to land tenure status affect to income distribution. The landtenure status are divided into owner operator, renter (cash tenant), and share-cropper operator (share tenant).The objective of this research were studied comparation of production, efficiency, and income distribution atfarming. This research analyze income distribution based on different land tenure and relationship inequalitywith poverty. This research use survey in data collecting and proportional stratified random sampling to choosesample. Analysis method and hypothesis test implement t-test and F-test from Cobb-Douglas function. Theresearch result showed efficiency and production rate of share-cropper operator was not too bad then owneroperator and renter (cash tenant). Land farm tenure has effect to income distribution, farmer who has widerland will have bigger income than other. Income inequality without other income higher than income whichinclude income outside farmer. Other income (outside farming) decrease income inequality.